Unveiling the cancer-fighting potential of Rheum species (Rhubarb): Phytochemistry, ethnopharmacology, and mechanistic insights into the anticancer effects of key anthraquinones - Umer Majeed Khaja; Chirag Chopra; Amit Sehgal; Reena Singh; Showkat Ahmad Ganie (Phytomedicine Plus)
Background: Rhubarb (Rheum spp.) has been cultivated for over 5,000 years for both medicinal and culinary purposes. Renowned in traditional and modern medicine, it offers a range of therapeutic benefits. The rhizome of rhubarb, recognized as a significant medicinal plant, was first documented as early as 270 BC in the ancient Chinese text “Shen Nong Ben Cao Jing”. Notably, rhubarb is celebrated for its anti-cancer properties, gastrointestinal regulation, anti-inflammatory effects, and ability to inhibit fibrosis. Cancer, a leading cause of global morbidity and mortality, underscores the urgency to identify new therapeutic agents. Despite rhubarb’s extensive history of use, there is a pressing need for a comprehensive review that examines its anti-cancer properties and underlying mechanisms. Purpose: This review aims to examine the phytochemistry, ethno-medicinal applications, and anti-cancer capabilities of Rhubarb. Additionally, it will explore the underlying mechanisms of the anti-neoplastic activity of the most prevalent anthraquinones found in Rheum species. Methods: A comprehensive search was conducted for randomized controlled trials on the benefits of Rheum species, using databases such as PubMed, Elsevier, SCOPUS, and the Cochrane Database for Systematic Review. Results: Rhubarb exhibits diverse biological effects through its phytoconstituents, making it effective in preventing and treating various diseases, including cancer. Key anthraquinones in rhubarb, such as emodin and aloe-emodin, have demonstrated the ability to inhibit cellular proliferation, induce apoptosis, and suppress metastasis in cancers of the breast, colon, lung, liver, blood, pancreas, stomach, and oral cavity. The chemopreventive and anti-carcinogenic potential of Rheum species stems from their modulation of critical molecular mechanisms and signaling pathways including NF-kappa B (NF-κB), Tumor Suppressor Gene (p53), tyrosine kinases, phosphoinositol 3-kinase (PI3K), mitogen-activated protein kinase (MAPK), protein kinase C (PKC) involved in various anti-cancer activities. The review findings also elucidate the potent anti-inflammatory activity of rhubarb, supported by various mechanisms including inhibition of lipoxygenase (LOX), cyclooxygenase (COX) and hyaluronoglucosaminidase (HYAL) enzymes, reduction of pro-inflammatory responses, and modulation of inflammatory signaling pathways. These findings highlight the therapeutic potential of rhubarb’s bioactive anthraquinones that show a great potential in fighting cancer and could be used for various therapeutic applications. Conclusions: Rhubarb contains herbal remedies that have the potential to prevent and treat a variety of human malignancies. Many chemical constituents of rhubarb, especially anthraquinones may be the cause of its therapeutic properties. The preclinical research discussed in this review strongly implies that Rheum species have a significant ability to prevent and treat human malignancies.